Paediatric acute retropharyngeal abscesses: An experience - Khan A Nazir; Patigaroo Amin Fozia; Mudasir ul Islam; Ahmed Shakil; Suhail Amin Patigaroo (Wolters Kluwer Medknow Publications, 2013)
Background: To describe our experience of paediatric patients with acute retropharyngeal abscess in terms of clinical presentation, diagnosis, management and complications. Materials and Methods: A prospective study was done for a period of 4 years (Jan 2009 to Jan 2013) on paediatric patients (< 15 years) with acute retropharyngeal abscess at two tertiary hospitals in Srinagar. Diagnosis was made on the basis of X-ray, CECT scan findings and confirmed on incision and drainage. Pus was aspirated from all patients and sent for culture and sensitivity. Data for clinical presentation, X-ray, CECT scan findings, causes, complications, bacteriology and management were collected. Thirty-five abscesses were drained while 5 with small abscesses on CECT were managed conservatively. Results: A total of 40 patients were diagnosed as acute retropharyngeal abscesses. Males were commonly affected, and most of the patients were less than 6 years of age. Most common symptom at presentation was fever (35) followed by neck pain (30) Dysphagia/odynophagia (22), swelling in neck (19). Most common clinical sign observed was oropharyngeal swelling and limitation of neck movements (30), cervical swelling/lymphadenopathy in 22 patients. Torticollosis and drooling were seen in 15 patients. Complications were seen in 8 patients. Most common X-ray finding was pre-vertebral thickening. Success rate with primary surgical drainage was 95% while 3 patients in conservative group failed. Conclusion: Children with RPA most commonly present with restricted neck movements, fever and cervical lymphadenopathy, and rarely with respiratory distress or stridor. Surgical intervention is necessary for most of these patients.